Investigation the effects of silver nanoparticles and gold nanoparticles on expression of bap and csu genes in biofilm formation of Acinetobacter baumannii - Niloofar Rezania; Parisa Rahmati; Fatemeh Noorbakhsh; Nazanin Farhadyar; Ensieh Lotfali (Iranian Journal of Microbiology, 2022)
Background and Objectives: Acinetobacter baumannii is one of the main pathogens of the hospital and causes various infections. csu A/BABCDE involved in the initial surface attachment during biofilm formation and bap gene produces specific proteins at the cell surface that play a direct role in formation of biofilm and the infectivity of this bacterium. The aim of this study was to investigate the effect of silver nanoparticles and gold nanoparticles on the expression of bap and csu genes in the Acinetobacter baumannii biofilm formation. Materials and Methods: The susceptibility test was performed to determine the MIC of silver nanoparticles, gold nanoparticles and gold- vancomycin nanoparticles performed by broth dilution method on A. baumannii strains. The ability of biofilms formation in strains treated by MIC of silver nanoparticles and gold- vancomycin nanoparticles were evaluated by microtiter plate method and A. baumannii ATCC19606 used as control. Expression of the csu and bap genes were determinded by measuring the cognate mRNA level by real-time PCR. Results: In present study, gold nanoparticles could not prevent the growth and biofilm formation of A. baumannii strains. The MIC concentration of silver nanoparticles and vancomycin- gold nanoparticles were 6.25 μg/ml and 0.625 μg/ml respectively and MBC concenteration of nanoparticles for 70% of strain was 12.5 μg/ml and 1.25 μg/ml respectively. Real-time PCR and data analysis, determined that the expression of bap, csuC and csuE genes in A. baumannii strains treated with MIC concentration (6.25 μg/ml) of silver nanoparticles decreased compared to control groups. Also, the expression of csuC and csuE genes in strains treated with MIC concentration (0.625 μg/ml) of vancomycin -gold nanoparticles increased, however the expression of bap was decreased compared to the control groups. Conclusion: Due to the inhibitory effect of silver nanoparticles and gold- vancomycin nanoparticles against A. baumannii biofilm formation and genes expression, they can probably be used for prevent of biofilm formation in medical instrument or can be use for treatment of infections with or without antibiotic.